Electricity prices through the lens of sentiments for the UN and the IMF: An asymmetric approach for Türkiye - Pinar Deniz; Thanasis Stengos (Borsa Istanbul Review)
This study examines the impact of the tone used in communication by two major international organizations, the United Nations (UN) and the International Monetary Fund (IMF), on electricity prices in Türkiye, an energy-dependent developing country with the highest-growing energy demand among member countries of the Organization for Economic Cooperation and Development (OECD). The empirical findings reveal that the effect of the communication tone of the two organizations on electricity prices differs, such that the IMF has a larger impact. Because of the significant impact of the communication tone by the IMF and the UN on the Turkish electricity market, the main policy recommendations to ensure energy security in Türkiye are decreasing dependence on the global markets, increasing credibility via sound domestic macroeconomic policymaking, increasing the share of renewable energy, and initiating a battery energy storage system.